An accurate and reliable positioning methodology for land vehicles in tunnels based on UWB/INS integration. (1st September 2022) - Kong, Xin; Li, Xu; Song, Xiang; Tian, Yuan; Kong, Dong
Abstract: At present, the global navigation satellite system (GNSS) is the most widely used technology in the field of vehicle navigation and positioning. However, due to satellite signal blocking, it can be challenging to obtain precise and reliable vehicle positions in completely GNSS-denied environments. In this paper, a positioning strategy utilizing ultra-wide band (UWB) and a low-cost MEMS inertial navigation system (INS) is proposed, aimed at tracking vehicles in typical GNSS-denied scenarios. UWB tech has potential for high-precision ranging due to its strong penetration ability. However, non-line-of-sight (NLOS) propagation still has a high occurrence in typical traffic scenarios due to the fact that the direct path between the radio transmitter and the radio receiver is obstructed. Therefore, a two-step NLOS error mitigation method is proposed to deal with the abnormal measurements of UWB in tunnels. First, a state-of-the-art probabilistic factor graph model is proposed to estimate the vehicle's position information based on UWB range measurements instead of excluding the NLOS reception. Then, a residual weighting algorithm is employed during UWB/INS loosely coupled integration to further mitigate the NLOS error. Finally, the performance of the proposed methodology is evaluated through experiments. Experiments conducted in the typical NLOS environment of Nanjing show that the proposed method can achieve higher positioning accuracy when compared with the conventional UWB/INS integration.